Using Electroencephalogram (EEG) to Understand The Effect of Price Perception on Consumer Preference - Aprilianty, Fitri; Purwanegara, Mustika Sufiati; Suprijanto, Suprijanto (The Asian Journal of Technology Management (AJTM), 2016)
Abstract. The research examines the influence of price as product cues on consumer’s perception and evaluation by using the application of electroencephalogram (EEG). This method can give objective information about consumer reactions towards product cues that will drive consumer’s choice. The main research objective was to observe and evaluate consumer’s brain activity in different brain regions while they were being exposed by several price levels (low, medium, high) of underwear as stimuli and focused mainly on liking/disliking the stimuli. The participants consist of 10 female and 10 male consumers within 18-24 years old, have normal vision, right handed, and considered as potential purchasers of underwear. The participant’s brain activity was collected using Emotiv EPOC neuroheadset (EEG) with international 10/20 system and was obtained in Beta frequency bands (13–30 Hz). The result indicated that there was a clear and significant change (p<0.05) in the EEG brain spectral activities of right and left hemisphere in the frontal (F3 & F4), temporal (T7 & T8), and parietal (P7 & P8) regions when participants indicated their attentiveness towards each price level stimulus. The results show, the male and female participant’s tactile sensations in parietal lobe does not give more favorable attention towards particular price stimulus, but the difference price perceptions in parietal lobe can lead to rational preference and give most favored response towards high price stimulus. Analyzing of price perception may help to understand the differences in price-related emotions and preference, which can gain insights into an alternative pricing strategy that can lead to influence consumers buying decision.Keywords:  EEG, Price, Perception, Preference, Underwear.